Evaluating causes and gestures: source-related and crossmodal features in the perception of environmental sounds - Sven-Amin Lembke (Frontiers in Psychology)
Communication through auditory cues often evokes associations to other sensory modalities. In film music, for instance, a descending pitch contour commonly resembles a falling motion. Such crossmodal associations to physical actions or shapes are here termed sound gestures and can naturally occur in environmental sounds. Little is known about how reliably listeners perceive gestures in such environmental contexts and how salient the gesture-relevant auditory feature needs to be. This article reports on an exploratory study concerning the identification of sound gestures by crossmodal matching using analogous visualizations. The study considered gesture-related factors, such as auditory salience and contour complexity, and explored whether a concurrent evaluation of features related to the environmental sound source or cause would affect gesture identification. Twenty untrained listeners evaluated sound gestures occurring in environmental sounds, e.g., pitch contour when switching a vacuum cleaner on and off, loudness contour of a ball dropping. Participants evaluated 28 environmental sounds in three variants (original, isolated gesture, hybrid) and had to identify the sound gesture among four visualized options while also inferring the underlying environmental source or cause through verbal description and rating their confidence in identifying the source/cause. Based on features describing the macro contour of gestures, participants correctly identified 81-83% of all gestures. Manipulated sounds that emphasized gesture salience yielded only slight improvements of identification accuracy compared to original environmental sounds. Participants were more confident in identifying the source/cause in sounds containing pitch gestures than those containing loudness gestures, while lexical and semantic diversity in describing underlying materials (source) and actions (cause) varied considerably. For both groups, however, measures for gesture identification and the evaluation of underlying materials and actions correlated only weakly, suggesting task independence. Overall, findings suggest that untrained listeners perceive sound gestures in environmental sounds and can reliably use them to form crossmodal associations, while also evaluating properties related to the sound source and cause. For one, the perception of environmental sounds may evoke crossmodal links, while the reliable identification of sound gestures highlights their utility to crossmodal control or search interfaces.